(untitled) (Medico Legal Update, 2021)
Polycystic ovary syndrome is define as illness in women that a reproductive age because common endocrinopathy and lead to reproductive dysfunction also infertility. PCOS is usually alignment with insulin resistance and metabolic syndrome, it is think that PCOS is the outcome of genetic effect addition to ecological factor. In this study (100) samples which divided into 40 samples of heath women and 60 samples of women with PCOS. It diagnosed by ovarian morphology on ultrasound also test the fasting blood sugar, insulin, insulin resistance and testosterone hormone by biochemical method also used molecular method to detect the genotype of TCF4 gene (rs290487) by RFLP-PCR technique. The results revealed that the frequency of allele T was recorded a highly significance (P<0.01) in patients (0.81%) while in control (0.89%), the frequency of allele C allele significant (P<0.01) in patients (0.19%) while in control (0.11%). We can be concluded from this study that the genetic variation in Iraqi women of gene (TCF4) was linked with PCOS while contrary in control (healthy women).